Komunikasi Interpersonal Orang Tua dalam Membangun Karakter Anak - Devia Aurelliani; Taufiq Furqon Nurhakim (Lembaga Pengembangan Kinerja Dosen, 2025)
Building a children’s character is an important aspect in the development of their personality in the future. In addition, building children’s character also requires a consistent and sustainable approach. Moral and ethical values are not enough to be taught theoretically, but must also be applied in everday life. And interpersonal communication can also strengthen children’s social skills. When parents or other family members become models of respectful communication, children will imitate this pattern in their interactions outside the home, such as the school or in the play environment. This study aims to determine how parental interpersonal communication builds children’s characterin Bojongla Village, Rancaekek Distict. The type of research used by the researcher is qualitative, namely using data obtained through in-depth interviews with three parents as the main informants who have elementary school aged children. The results of the study showed that interpersonal communication carried out by parents to children includes verbal and nonverbal communication, with a communication style that is open, empathetic, and supportive.